CULTURAL REPRESENTATION IN THE POETRY GROUP " THE PEN'S CREATION OF BORNEO" RIFFATERE STUDY - Ilham, Muhammad Ilham; Wijiati, Iva Ani (JURNAL KONFIKS, 2025)
The research is a form of attention to the culture of the Tidung tribe which has a significant role as a culture that has distinctive characteristics in Indonesia but is threatened with extinction due to coexistence with transmigration communities and the influence of globalization. This research focuses on the representation of the ethnic culture of the Tidung tribe in the poem "Bucin" Culture and Love by border students in North Kalimantan, namely the introduction, perception, and meaning given by individuals in local context groups. This research uses an analysis of 7 cultural elements in the Tidung tribe through poetry verses. The research method used in this research is descriptive qualitative through the analysis techniques of identification, analysis, and conclusion. Based on the results of the research analysis, it was found that 3 cultural elements (social organizations, livelihoods, local-scale arts, and language in the Bucin poetry collection "Culture and Love" have their own characteristics. Social organizations with an attitude of openness, simplicity, and mutual respect for differences. Livelihoods with the characteristics of producing ironwood/red wood and carvings as a community living on the coast. Art as a characteristic of Tidung culture as a form of conveying the meaning of all forms, objects, and colors used in it. Furthermore, language has characteristics as diction used according to the type of ritual of the Tidung tribe.